ANALYSIS OF PHONOLOGICAL ERRORS IN THE SHORT STORY ANGSA PUTIH WAS NOT ALWAYS WHITE BY STUDENTS OF SMAN 10 TASIKMALAYA - Ahmad Taufik; Winda Murni; Hilwa Hamya Aulia; Aveny Septi Astriani (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This research aims to analyze phonological language errors in the short story "Not Always White Swan" by Nadia Fitriantika, a student from SMAN 10 Tasikmalaya. Emphasizing the crucial role of language in daily communication, the study focuses on phonological errors as an integral part of both formal and non-formal language learning. descriptive qualitative method, employing the observe and note technique, is utilized to determine, explain, classify, and evaluate phonological errors in the short story. The analysis reveals instances of phonemic addition, deletion, and modification, such as the addition of the phoneme in the word "moment," deletion in the word "still," and modification in the word "closet." This research contributes to understanding how phonological language errors can impact readers' comprehension of the short story. The analysis serves as a valuable evaluative tool and provides insights into the author's expression in crafting literary works. In conclusion, this study underscores the importance of precise language use, emphasizing the role of phonology in conveying a clear message in literary works.